A teaching case on implementing an activity-based costing system in a service firm: Lakhiru Insurance Company. (21st May 2010) - Herath, Siriyama Kanthi; Wickramasinghe, Danture; Indrani, M.W.
In recent years, increasing emphasis has been placed on the need for accounting students to view problems in their organisational and social context and accounting educators have started to use cases widely as a teaching method. Cases provide students with high-levels of reasoning, problem solving, and communication skills. They bring students to real world scenarios allowing them to learn by practising. Many cases are designed to provide students and the instructor with lively and integrative learning environments. They support longer retention of theories, and understand their practical implications. The objective of this instructional case is to motivate instructors of management accounting to use cases in class, and also to increase students' knowledge of the importance of activity-based costing (ABC) information for managerial decision making in service contexts. The case discusses how distorted cost information can lead to poor management decisions and how ABC system can provide more accurate information for decision making to managers in a service firm.